Highly photoactive rGO-MnO2/CuO nanocomposite photocatalyst for the removal of metanil yellow dye and bacterial resistance against Pseudomonas Aeruginosa - A. Ceril Jeoffrey; S. Jothi Ramalingam; K. Murugaiah; A.R. Balu (Chemical Physics Impact, 2023)
The superior photocatalytic, biological, and electrochemical properties of metal oxide nanocomposites have made them an important part of contemporary nanotechnology research. Nanocomposite involving MnO2 and CuO has been widely utilized for catalytic and electrochemical applications. However, the different oxidation states of MnO2 and lower band gap of CuO limits the efficiency of the devices involving the composite of these two semiconductors. As a result, reduced graphene oxide (rGO) is integrated into the MnO2/CuO matrix. rGO-MnO2/CuO and MnO2/CuO nanocomposites (NCs) were synthesized using one-pot green synthesis and chemical precipitation respectively. rGO decorated MnO2/CuO NC was green synthesized from graphene oxide using Alternanthera sessilis leaf extract. XRD detected peaks related to orthorhombic structured MnO2 and monoclinic structured CuO for both the composites. Star shaped nanostructures are observed for rGO incorporated MnO2/CuO nanocomposite. MC and rMC composites have band gaps of 2.16 and 2.04 eV, respectively. FTIR spectrum showed the characteristic peaks for MnO2 and CuO in the rGO-MnO2/ CuO composite. Raman active Ag and Bg CuO modes occur at 270 and 450 cm−1 and Mn-O symmetric vibrations at 590 and 540 cm−1. The incorporation of rGO into the MnO2/CuO composite increased its photocatalytic activity from 87 % to 96 % against the degradation of metanil yellow dye by increasing its electron conductivity, adsorption capacity, and light absorption capacity. The MnO2/CuO nanocomposite with rGO demonstrated enhanced antibacterial activity, with a zone of inhibition of 24 mm compared to 13 mm for the control and 18 mm for the MnO2/CuO composite.